2017
DOI: 10.1089/neu.2016.4591
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Integrity of Hippocampal Subregions Is Impaired after Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) affects a large number of individuals and diffusion tensor imaging can be used to investigate microstructural integrity of brain tissue after mTBI. However, results have varied considerably between studies and gray matter (GM) integrity has been largely neglected in these investigations. Given impaired working memory processing after mTBI and its possible association with Alzheimer's disease, we investigated hippocampal integrity and parcellated this structure into five subre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The spatiochemical changes in different brain regions after TBI and therapeutic treatment have been investigated in lots of previous studies by MSI techniques, , , and the injured area of brain at acute phase of the model were usually of interest. However, it has been reported that at chronic phase of TBI, the lesions could be diffused to other regions of the brain due to impaired response inhibition resulting in a partial breakdown of structures and reactive gliosis, ,, so the chemical changes outside of the injured area at chronic phase of TBI are also worth investigation. The score plots of PCA (Figure ) clearly show that the TBI group and Sham group were more clustered, especially for hippocampus area, and have observable separation in the y axis for some areas such as CP, MB, and TH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiochemical changes in different brain regions after TBI and therapeutic treatment have been investigated in lots of previous studies by MSI techniques, , , and the injured area of brain at acute phase of the model were usually of interest. However, it has been reported that at chronic phase of TBI, the lesions could be diffused to other regions of the brain due to impaired response inhibition resulting in a partial breakdown of structures and reactive gliosis, ,, so the chemical changes outside of the injured area at chronic phase of TBI are also worth investigation. The score plots of PCA (Figure ) clearly show that the TBI group and Sham group were more clustered, especially for hippocampus area, and have observable separation in the y axis for some areas such as CP, MB, and TH.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, though changes of some particular lipids outside the injured site were mentioned in previous studies, , all these studies for TBI were focused on the injured site of the brain. However, it has been reported that secondary brain injury at chronic phase of TBI occurred not only in the trauma region but also in other tissue regions such as the distant hippocampus, basal ganglia, and thalamus. , …”
Section: Introductionmentioning
confidence: 99%
“…Our findings extend previous studies of pediatric TBI that noted reduced FA in a variety of limbic pre-frontal pathways, including the cingulum bundle, 35,61 uncinate fasciculus, 41 frontal lobe WM, 62 the centrum semiovale, corona radiata, and temporal lobe WM relative to either typically developing children 63 or those with orthopedic injuries. [64][65][66][67] Because of the vulnerability of the hippocampus to disruption by TBI, 27,29,[68][69][70] we anticipated that FA from pathways seeded in the hippocampus and hippocampal MD would be reduced in the TBI group compared with the EI group. Based on the GCS score, severity of TBI was significantly associated with decreased FA in a number of pathways and increased MD in the hippocampus and amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In children with TBI, frontal and temporal lobes are common sites of injury. Consequently, the hippocampus 27 and PFC 28 are vulnerable particularly to disruption. Smaller total or regional hippocampal volumes have been noted during both subacute 29 and long-term follow-up.…”
Section: Structural Neuroimaging Of Stress Systems In Children With Pmentioning
confidence: 99%
“…However, injury is common in the frontal and temporal lobes, producing deficits in executive functioning, processing speed, social cognition, and memory ( Stuss, 2011 ). People with both mild ( Leh et al, 2017 ) and moderate-severe TBI ( Rigon et al, 2019 , 2020 ) frequently demonstrate memory deficits. People with TBI also often have poor social outcomes ( Wehman et al, 1993 ; Engberg and Teasdale, 2004 ; Kelly et al, 2008 ) which create barriers to community reintegration.…”
Section: Gesture In Neurogenic Communication Disordersmentioning
confidence: 99%